Urogynaecology - Jefferis, Helen; Price, Natalia; Collins, Sally (Obstetrics specialist) (Oxford : Oxford University Press, 2020)
The Oxford Specialist Handbook of Urogynaecology is a compact and comprehensive guide to all aspects of pelvic floor function and dysfunction. Ideal for the Gynaecology trainee, it includes approaches to assessment and management in all compartments, as well as chapters on special groups such as children and the elderly.
Includes index.
Sally Collins is an editor, not a co-author.
Specialized.
Description based on online resource; title from home page (viewed on March 27, 2020).
Keywords: Urinary organs -- Diseases; Pelvis -- Diseases